2001
DOI: 10.1126/science.1063037
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotopes and the Moon-Forming Giant Impact

Abstract: We have determined the abundances of 16O, 17O, and 18O in 31 lunar samples from Apollo missions 11, 12, 15, 16, and 17 using a high-precision laser fluorination technique. All oxygen isotope compositions plot within +/-0.016 per mil (2 standard deviations) on a single mass-dependent fractionation line that is identical to the terrestrial fractionation line within uncertainties. This observation is consistent with the Giant Impact model, provided that the proto-Earth and the smaller impactor planet (named Theia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
226
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(236 citation statements)
references
References 16 publications
9
226
0
1
Order By: Relevance
“…Yet, in the giant impact model, the Moon forms from a mixture of material derived from two separately formed objects: the impactor and the target protoearth. It had been suggested that an impactor formed in an orbit close to that of the Earth could have had the same oxygen composition as the Earth, because observed oxygen compositions vary with heliocentric position [12,13]. This seemed to agree well with the canonical impact (see below) that requires a low impact velocity and therefore an impactor orbit similar to that of the Earth.…”
Section: (A) Constraintssupporting
confidence: 74%
See 1 more Smart Citation
“…Yet, in the giant impact model, the Moon forms from a mixture of material derived from two separately formed objects: the impactor and the target protoearth. It had been suggested that an impactor formed in an orbit close to that of the Earth could have had the same oxygen composition as the Earth, because observed oxygen compositions vary with heliocentric position [12,13]. This seemed to agree well with the canonical impact (see below) that requires a low impact velocity and therefore an impactor orbit similar to that of the Earth.…”
Section: (A) Constraintssupporting
confidence: 74%
“…The Earth and Moon have identical oxygen isotope compositions to within measurement precision, which are quite distinct from those of most meteorites and Mars [12]. Yet, in the giant impact model, the Moon forms from a mixture of material derived from two separately formed objects: the impactor and the target protoearth.…”
Section: (A) Constraintsmentioning
confidence: 99%
“…Because the formation of the Moon requires a relatively low-velocity impact between Theia and the proto-Earth, it had previously been argued that Theia likely resided in an orbit very similar to the proto-Earth and may have formed from a similar region of the planetesimal disk (Wiechert et al 2001). If Theia and Earth formed from the same pool of planetesimals, they may have a similar composition, while Mars and Vesta have distinctly different oxygen signatures, owing to their different feeding zones in the planetesimal disk.…”
Section: Theia and The Moon-forming Impactmentioning
confidence: 99%
“…The lunar-forming impact was probably also the last major event in the Earth's accretion: substantial addition of material after the Moon-forming impact would tend to make the Moon too iron rich (Canup 2004a), and even if such later accretion was limited to the Earth, it would probably cause the Earth's O-isotope composition to diverge from that of the Moon (e.g. Wiechert et al 2001).…”
Section: The Moon-forming Impactmentioning
confidence: 99%
“…Wiechert et al 2001). This appears to require either that the impactor and proto-Earth had identical compositions (unlikely, given the compositional variation predicted by accretion models) or that extensive mixing between proto-lunar and proto-Earth material after the impact but prior to the Moon's formation allowed compositions to equilibrate (Pahlevan & Stevenson 2007).…”
Section: (C ) Implications and Open Issuesmentioning
confidence: 99%